PENGAWASAN DAN PENGENDALIAN HEWAN TERNAK LIAR OLEH DINAS PETERNAKAN KABUPATEN KUANTAN SINGINGI TAHUN 2012-2013 - Zullia Fitriani; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Animals are not in a well maintained a syimpton of society in various regions and these phenomena polemical and losses for various parties, this phenomenon also accurs in Kuantan Singingi that has generated a lot of problems among which is a loss to society of road users due to animal cattle that roam the streets kingdom, causing an accident. The authors wanted to axamine further on monitoring and control of the wild animal husbandry depatement in Kuantan Singingi year 2012-103.Informant in this study is the administrative department of animal husbandry and civil service police unit Kab. Kuantan Singingi, members of Parliament KAb. Kuantan Singingi, as well as chairman of the advisory board of the institute adat Melayu Riau, and liverstock owners are determined by purposive according to research needs. This study aims to determine the cause of the ineffectiveness of supervision on animal husbandry department in Kuantan Singingi Wild Years 2012-2013.In this study, the authors used qualitative methods to analysis. Data collection techniques in this study is the observation and interviews, while the technical analysis of the data that is using a qualitative analysis, by analyzing the expression or records available or observed behavior. Qualitative analysis was performed on the data, in this case the qualitative data in the form of information, in the form of language prose description,then associated with other data to obtain clarity on the truth.Conclussions and control of animal wild by Kuantan Singingi district veterinary office is not running optimally, due to lack of facilities and infrastructure, and they also have not been able to curb roaming liverstock due ti the habits of the community malope tradition.Key Words : Control, Control, and Liverstock